Legal Position of Village-Owned Enterprises as Legal Entities in Indonesian Legislation: Kedudukan Hukum Badan Usaha Milik Desa Sebagai Badan Hukum Dalam Peraturan Perundang-undangan di Indonesia - Purwaningsih, Sri Budi; Mediawati , Noor Fatimah; Mursyidah, Lailul (Procedia of Social Sciences and Humanities, 2022)
. Lemujut Sejahtera Village Owned Enterprise (BUMDesa) is a business entity owned by the Lemujut Village Government, Krembung District, Sidoarjo Regency which was established on the basis of village consultations between the village government, the community and the Village Consultative Body (BPD) as outlined in the Village Regulation (Perdes). This village regulation has become legal standing, meaning that it is the legal basis for the establishment of BUMDes, so since then BUMDes have had the status as legal subjects: legal entities (rechpersoon). This study aims to determine whether the BUMDes of Lemujut Sejahtera is a legal entity according to the laws and regulations in Indonesia? The method used in the research is legislation (statute approach). The results of this study conclude that the BUMDes of Lemujut Sejahtera is a legal entity according to the laws and regulations in Indonesia, especially as a private legal entity in terms of civil purposes. The implication of BUMDes as a legal entity is that it can carry out certain legal actions that give rise to legal relations between BUMDes and parties in the civil field or the business world.